2016
DOI: 10.1111/aji.12613
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection of Hofbauer cells

Abstract: Recent studies have linked antenatalinfection with Zika virus (ZIKV) with major adverse fetal and neonatal outcomes, including microcephaly. There is a growing consensus for the existence of a congenital Zika syndrome (CZS). Previous studies have indicated that non-placental macrophages play a key role in the replication of Dengue virus (DENV), a closely related flavivirus. Since the placenta provides the conduit for vertical transmission of certain viruses, and placental Hofbauer cells (HBCs) are fetal-placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 52 publications
3
93
0
7
Order By: Relevance
“…This is particularly true after the first trimester of human pregnancy, when the placenta undergoes dramatic morphologic changes, the most notable of which is the establishment of a hemochorial placenta (i.e ., fetal-derived placenta in direct contact with maternal blood). The detection of ZIKV RNA in placental trophoblasts (most commonly cytotrophoblasts), Hofbauer fetal-derived macrophages, and fetal endothelial cells (Jurado et al, 2016; Miner et al, 2016; Quicke et al, 2016; Richard et al, 2017; Simoni et al, 2017; Tabata et al, 2016) is strongly suggestive of a transplacental route of transmission. Given that fetal-derived syncytiotrophoblasts form a key cellular barrier to the hematogenous spread of ZIKV at a variety of gestational stages, ZIKV likely has evolved a mechanism to bypass the placental villous barrier for vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true after the first trimester of human pregnancy, when the placenta undergoes dramatic morphologic changes, the most notable of which is the establishment of a hemochorial placenta (i.e ., fetal-derived placenta in direct contact with maternal blood). The detection of ZIKV RNA in placental trophoblasts (most commonly cytotrophoblasts), Hofbauer fetal-derived macrophages, and fetal endothelial cells (Jurado et al, 2016; Miner et al, 2016; Quicke et al, 2016; Richard et al, 2017; Simoni et al, 2017; Tabata et al, 2016) is strongly suggestive of a transplacental route of transmission. Given that fetal-derived syncytiotrophoblasts form a key cellular barrier to the hematogenous spread of ZIKV at a variety of gestational stages, ZIKV likely has evolved a mechanism to bypass the placental villous barrier for vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Such cells originate in the yolk sac, fetal liver, and bone marrow 169171 and can colonize developing organs to become tissue residents which persist until adulthood 172 . During pregnancy, Hofbauer cells (fetal macrophages) reside in the placental villous tree 173175 , indicating that this can be a potential source for amniotic fluid macrophages. In cases with intra-amniotic infection/inflammation, monocytes/macrophages are abundant and expressed high levels of IL-1α and IL-1β 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardinal features of ZIKV, of critical clinical importance are that (i) it is transmitted by a mosquito bite but can also be transmitted sexually, (ii) it is able to actively cross the placental barrier and replicate in the placenta, and (iii) it can disseminate to the fetus and its developing brain, where it leads to severe neurodevelopmental defects, in particular in the developing cortex, resulting in microcephaly. Studies of cell and tissue samples from infected humans, as well as experimentally infected NHP and mouse lines, have shown that ZIKV infects a wide variety of tissues and cells, including the skin (human dermal fibroblasts, epidermal keratinocytes, and immature dendritic cells) (Hamel et al, 2015), the testis (Leydig cells, sertoli cells, spermatogonia) (Govero et al, 2016; Ma et al, 2016), vaginal epithelium and uterine fibroblasts (Yockey et al, 2016; Chen et al, 2016), placenta (trophoblasts, endothelial cells, Hofbauer cells) (Noronha et al, 2016; El Costa et al, 2016; Simoni et al, 2017; Quicke et al, 2016), and the brain (cortical progenitors, mature neurons and astrocytes) (Gabriel et al, 2017; Li et al, 2017; Qian et al, 2016; Tang et al, 2016; Xu et al, 2016; Brault et al, 2016). It may also infect the eye (Ganglion cells, bipolar neurons, the optic nerve, cornea) and be found in body fluids including tears, saliva, semen, cervical mucus and urine (Miner et al, 2016a; Barzon et al, 2016; Zambrano et al, 2017).…”
Section: Mechanisms and Consequences Of Maternal-fetal Transmissionmentioning
confidence: 99%
“…Once in the placental tissue, ZIKV replicates in Hofbauer cells, the resident macrophages of the placenta; this has been observed in clinical samples of human placentas, in human placental explants infected experimentally, and in cultured Hofbauer cells. ZIKV replication in Hofbauer cells (Simoni et al, 2017; Quicke et al, 2016; Tabata et al, 2016), as well as infection of endothelial cells of placental villus capillaries may constitute key amplification steps and lead to prolonged viral release in the fetal circulation, from where ZIKV can disseminate to the brain (Noronha et al, 2016; Vermillion et al, 2017; Tabata et al, 2016; Richard et al, 2017). …”
Section: Mechanisms and Consequences Of Maternal-fetal Transmissionmentioning
confidence: 99%
See 1 more Smart Citation